HOME BLEACHING TECHNIQUE USING CARBAMIDE PEROXIDE - Rahmi Alma Farah Adang; Endang Suprastiwi; Munyati Usman (Journal of Dentistry Indonesia, 2015)
There are two basic kinds of tooth whitening agents. The first is over the counter materials and the other is material used by the dentist or under dentist control. Home bleaching is a technique using 10% carbamide peroxide on a tray applied by patient under dentist supervision. This paper is a review of the effect of 10% carbamide peroxide home bleaching technique. It is revealed that this method is simple, safe, economic, and has short chairside time.